Physical Fabrication of Metallic Nanoparticles: Methods, Mechanisms, Control Variables, Emerging Trends - Israa A. Hammed; Thaer A. Mezher (Indonesian Journal of Material Research, 2026)
Physical methods for synthesizing metal nanoparticles (MNPs) are of significant importance because the resulting nanomaterials can be produced with high purity, minimal chemical bonding, and well-defined structural characteristics. In these approaches, metals are transformed from the solid state into atomic or plasma states using external energy sources such as heat, electricity, plasma, or light. The generated species are then rapidly cooled, leading to agglomeration and the formation of nanoparticles. This study focuses on the principal physical techniques employed for metal nanoparticle fabrication, including inert gas condensation, magnetron sputtering, spark discharge, and laser ablation in liquids. The fundamental physical mechanisms governing nanoparticle formation—such as vapor supersaturation, homogeneous nucleation, coagulation, agglomeration, and surface diffusion—are discussed in detail. Furthermore, the influence of key process parameters on nanoparticle properties, including particle size, shape, crystal structure, composition, and surface chemistry, is systematically examined. A comprehensive comparison of these techniques is provided, highlighting their advantages, limitations, scalability, and suitability for various applications. Finally, emerging challenges and future perspectives are addressed, including real-time process control, the synthesis of high-entropy multicomponent nanoparticles, and the implementation of green chemistry principles in large-scale nanoparticle production.